Tailoring chemical and physical properties of fibrous scaffolds from block copolyesters containing ether and thio-ether linkages for skeletal differentiation of human mesenchymal stromal cells. (January 2016) - Chen, Honglin; Gigli, Matteo; Gualandi, Chiara; Truckenmüller, Roman; van Blitterswijk, Clemens; Lotti, Nadia; Munari, Andrea; Focarete, Maria Letizia; Moroni, Lorenzo
Abstract: Bioactive scaffolds for tissue engineering call for demands on new materials which can enhance traditional biocompatibility requirements previously considered for clinical implantation. The current commercially available thermoplastic materials, such as poly(lactic acid) (PLA), poly(glycolic acid) (PGA), poly(ε-caprolactone) (PCL) and their copolymers, have been used to fabricate scaffolds for regenerative medicine. However, these polymers have limitations including lacking of broadly tuning mechanical and degradable properties, and activation of specific cell-scaffold interactions, which limit their further application in tissue engineering. In the present study, electrospun scaffolds were successfully fabricated from a new class of block poly(butylene succinate)-based (PBS-based) copolyesters containing either butylene thiodiglycolate (BTDG) or butylene diglycolate (BDG) sequences. The polyesters displayed tunable mechanical properties and hydrolysis rate depending on the molecular architecture and on the kind of heteroatom introduced along the polymer backbone. To investigate their potential for skeletal regeneration, human mesenchymal stromal cells (hMSCs) were cultured on the scaffolds in basic, osteogenic and chondrogenic media. Our results demonstrated that PBS-based copolyesters containing thio-ether linkages (i.e. BTDG segments) were more favorable for chondrogenesis of hMSCs than those containing ether linkages (i.e. BDG sequences). In contrast, PBS-based copolyesters containing ether linkages showed enhanced mineralization. Therefore, these new functional scaffolds might hold potential for osteochondral tissue engineering applications.